Perancangan Aplikasi Marketplace Meal Kit Sebagai Upaya Mendukung Pola Hidup Sehat dan Reduksi Sampah Makanan - Lim, Chandra; Hariandja, Johanna (Universitas Katolik Parahyangan, 2025)
During pandemic, the increase in healthy lifestyle adoption through home cooking has led to a significant surge in household food waste, with a percentage up to 37%. One of the viable solutions that could be applied is using meal kit which potentially curbing 1,24 million tons of food waste annually. Based on the survey and interviews, respondents are interested in meal kit marketplace application as an effort to support healthy lifestyles and reduce food waste. The method used to design the application is interaction design lifecycle model. The needs identification that was done by semi-structured interviews generates 13 groups of primary customer’s needs and 7 seller's needs. The results of identified needs was made into 3 alternative design plans, be it for the buyers or sellers. The selected alternative design is developed into high-fidelity prototype named FoodLab. The prototype is evaluated using task completion and SUS questionnaire. For the buyers, they have an average effectiveness criteria of 88%, efficiency criteria of 83,67%, and SUS score of 80,71. For the sellers, they have an average effectiveness criteria of 100%, efficiency criteria of 100%, and SUS score of 90. The SUS value has crossed the acceptance value of 68, while the effectiveness and efficiency are in the very effective and efficient category (>80%). Based on the evaluation result, several improvement were planned, such as increasing the button and font size, attaching portion information, and providing cooking tutorial video pages.